Pengetahuan Dengan Kepatuhan Minum Tablet Tambah darah Pada Remaja Putri - Nengah Runiari; Ni Nyoman Hartati (Jurnal Gema Keperawatan, 2020)
The aim of this study was to determine the relationship between knowledge and adherence to taking blood supplemented tablets for girls. The research design was correlational analytic with cross sectional approach. The number of samples was 149 students of class XI SMA 6 Denpasar who were selected by total sampling technique. The instruments used in this study were a knowledge questionnaire and the MMAS-8 (Morisky Medication Adherence Scale) to measure adherence to taking blood supplemented tablets. The results showed that the knowledge level of the respondents was mostly in the good enough category as much as 44.3%. It was found that 21.5% of respondents had poor knowledge. The level of adherence of respondents to drink iron tablets was 87 people (58.4%) with low adherence and 62 people (41.6%) had moderate adherence. The results of the analysis with Kendall Tau found a p-value of 0.03, which means that there is a relationship between knowledge and adherence to taking blood supplement tablets. Furthermore, it is suggested to increase the involvement of parents in monitoring the drinking of iron tablets.